Open Journal System (OJS) As An Office Automation Model - Elya Riska Dwi Wahyuni; Titi Susanti; Dwi Noviana Purnamasari; Rina Rakhmawati; Walda Khoiriyah (Diplomatika: Jurnal Kearsipan Terapan, 2021)
The phenomenon of the COVID-19 pandemic forces the world community to transform into the world of work through the implementation of work from home. Many offices, especially in Indonesia, make use of various information systems and applications to facilitate work. Automation studies in the office environment are being studied again. The classic problem faced by most offices in Indonesia is that the automation system used is not integrated, one of which is the filing system. Most filing systems are limited to storing databases and tracking information. The archiving system model that is considered integrated, not limited to database storage and information retrieval, is the open journal system used by Indonesian national journals. This study aims to analyze the open journal system as a model for implementing the concept of office automation. The research object used is the open journal system used by accredited national journals in the social and humanities field. Data obtained through participatory observation of the open journal system used, in-depth interviews with journal managers, and literature studies. The data were processed and analyzed using the data triangulation approach. The results showed that the open journal system is an implementation of the concept of comprehensive office automation. However, it is necessary to conduct a study regarding the security and authentication of the metadata that is created on the system.